Unlocking Financial Prosperity: The Power of Strategic Saving Habits - Wayan Suryathi; Andes Goutama; Lioni Indrayani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research investigates the intricate interplay between strategic saving habits, income level, financial planning, and financial prosperity among customers at KEB Hana Bank Bali. Utilizing a quantitative approach with 80 randomly sampled bank customers, the study employs path analysis and Smart PLS to analyze the direct and indirect effects of these variables. The findings reveal a significant positive association between strategic saving habits and financial prosperity, mediated by financial planning, highlighting the importance of disciplined saving behaviors and professional financial guidance in achieving financial well-being. While income level directly influences financial prosperity, its impact is not significantly mediated by financial planning in this context. These insights underscore the importance of promoting strategic saving habits and facilitating access to comprehensive financial planning resources across diverse income levels to empower individuals in achieving their financial goals and fostering long-term prosperity.